Country Partnership Framework for the Republic of Madagascar for the Period of FY17-FY21 - World Bank; International Finance Corporation; Multilateral Investment Guarantee Agency (World Bank, Washington, DC, 2017)
This Country Partnership Framework (CPF) sets out the World Bank Group’s (WBG) strategy in Madagascar for the period of FY17‐FY21. As the country has emerged from a political crisis, the CPF supports the Government’s goal of generating a higher, inclusive and sustainable growth path to reduce poverty, as presented in its 2015‐2019 National Development Plan (NDP). The expanded resources and the larger range of instruments available under IDA18 enable the WBG to support the Government in putting the country on a higher development trajectory, by investing at scale in a few areas that could unlock Madagascar’s development. Success in achieving ambitious goals, such as doubling the rate of electricity access, will hinge on the authorities’ ability to sustain reforms while addressing some of the causes of the country’s cyclical instability. The program proposed under this CPF seeks to increase the resilience of the most vulnerable people and to promote inclusive growth, while strengthening national and local institutions so as to reduce fragility. Risks to achieving those objectives continue to be substantial and will require the WBG to adopt a flexible approach. First, the nascent rebound in economic growth has not yet been felt by a large majority of the population. The depth of poverty is also such that extreme climate events could quickly reverse the small gains achieved since 2014 and fuel social tensions. Second, presidential elections are expected to take place in late 2018. They could generate a slowdown in the adoption of reforms and lead to a rise in political tensions. Recent crises have occurred around elections and thus the possibility of another crisis cannot be excluded. Finally, it remains to be seen if the Government will be able to address the roots of the country’s fragility and change the bargain between the elites and the rest of the population, including by creating a more level playing field for the private sector. These risks will require the WBG to monitor closely the country context and be ready to adapt its approach throughout the CPF period.